A comparison of sporadic and familial multiple sclerosis. - Weinshenker, BG; Bulman, D; Carriere, W; Baskerville, J; Ebers, G (1990)
We compared demographic and clinical features, including outcome defined by a failure time analysis of disability, in 143 patients with a family history of multiple sclerosis (familial MS) compared with 956 patients without such a history (sporadic MS). Patients with familial MS did not differ from those with sporadic MS even when patients with 1st-degree relatives or multiple relatives with MS were considered separately. An intraclass correlation analysis of 13 pairs of affected 1st-degree relatives, both members of which were followed in our clinic, failed to reveal heterogeneity among different families. We were unable to find any support for differences between familial and sporadic MS.